2001
DOI: 10.1021/ja004292f
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of Uniquely Folded Mini-Protein Motifs:  Development of a Homotrimeric ββα Peptide

Abstract: The discovery of a discretely folded homotrimeric betabetaalpha motif (BBAT1) was recently reported (J. Am. Chem. Soc. 2001, 123, 1002-1003). Herein the design, synthesis, and analysis of a small library of peptides which led to the isolation of BBAT1 is described. betabetaalpha peptides based on the monomeric sequence of BBA5 (Folding Des. 1998, 120, 95-103) were synthesized to include the anthranilic acid/nitrotyrosine fluorescence quenching pair to rapidly detect interpeptide association. In the first gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 32 publications
2
59
0
2
Order By: Relevance
“…2A) on the highly acid-labile TGT resin. The peptides were released from the resin with a C-terminal carboxylic acid and side-chain protection intact, and were subsequently derivatized to afford the corresponding C-terminal thioesters (Futaki et al 1997;Mezo et al 2001). The cpTyr building block was synthesized as previously described (Rothman et al 2003) to install a pTyr masked by the 1-(2-nitrophenyl)-ethyl (NPE) caging group.…”
Section: Resultsmentioning
confidence: 99%
“…2A) on the highly acid-labile TGT resin. The peptides were released from the resin with a C-terminal carboxylic acid and side-chain protection intact, and were subsequently derivatized to afford the corresponding C-terminal thioesters (Futaki et al 1997;Mezo et al 2001). The cpTyr building block was synthesized as previously described (Rothman et al 2003) to install a pTyr masked by the 1-(2-nitrophenyl)-ethyl (NPE) caging group.…”
Section: Resultsmentioning
confidence: 99%
“…17 In the current studies we used the highly acid-labile carboxytrityl linker to the solid support (TGT-resin) to access the C-terminal thioester as previously introduced by our laboratory. 18 In a similar approach, other groups have employed 2-chlorotrityl linkers. 19 Highly acid-labile resin linkers allow orthogonal cleavage from the resin under mild acidic conditions without deprotection of amino acid side chains.…”
Section: Spps Of the Unglycosylated And Glycosylated Thioesters 1-28 mentioning
confidence: 99%
“…Because it has been reported that shortening the linker between domains favors domain-swapped oligomers (19, 20), we introduced a bias toward oligomerization in the BBA motif by varying the length of the 3-aa hinge region between secondary structural elements (21). Our approach for the discovery of homooligomers of peptides with ␤␤␣ supersecondary structure was based on a complementary design and screening process (21,22). BBAT1 (21, 22), a homooligomeric peptide, and the Gly9DAla analog, 1 (23) ( Table 1), share many characteristic features of larger proteins, including cooperative folding, lack of 1-anilino-8-naphthalene sulfonate binding, and limited deuterium exchange.…”
mentioning
confidence: 99%
“…Because it has been reported that shortening the linker between domains favors domain-swapped oligomers (19,20), we introduced a bias toward oligomerization in the BBA motif by varying the length of the 3-aa hinge region between secondary structural elements (21). Our approach for the discovery of homooligomers of peptides with ␤␤␣ supersecondary structure was based on a complementary design and screening process (21,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation